فترة الثمانينات نموذجا: القناع النبوي في الشعر الجزائري المعاصر - إعداد الطالبة: فــــــــــيروز شـــــــريفي, مشرفا ومقررا عباس بن يحي (My University, 2021)
الملخص : تسعى هاته الدراسة للبحث في تقنية القناع النبوي في الشعر الجزائري المعاصر ،بوصف التقنية عموما أداة فعالة و مهمة نهضت بتجارب شعرية عديدة، فقد رصدت الدراسة تجليات القناع النبوي في الشعر الجزائري المعاصر فترة الثمانينيات تحديدا،و عند شاعرين جزائريين الأخضر فلوس و عثمان لوصيف عبر مدخل نظري و ثلاثة فصول تطبيقية،خصص المدخل لتحديد مفهوم القناع و تقصي أصوله التاريخية ثم أدبيته وحدوده ،واقتصر الفصل الأول على تقنية القناع في الشعر العربي المعاصر دوافعا وأنواعا و فعالية،الفصل الثاني كان عن تجليات القناع النبوي في الشعر الجزائري المعاصر ومقاربة نصوص شعرية للأخضر فلوس وعثمان لوصيف نهضت على التقنع بشخصيات نوح،أيوب ، موسى، وإبراهيم عليهم السلام ،وخاتم الأنبياء عليه الصلاة و السلام،الفصل الثالث كان عن الخصائص البنائية(أشكال الإفادة) لقصيدة القناع وجمالياتها. Summary: The present study seeks to research the technique of the prophetic mask in contemporary Algerian poetry, describing the technique in general as an important phenomenon of modern Arabic poetry, and an effective tool that developed many poetic experiences. In fact, the study detected the manifestations of the prophetic mask in contemporary Algerian poetry in the eighties in particular, and among the poets LAKHDAR FELLOUS and OTHMAN LOUCIF in a theoretical chapter as an introduction and three chapters. The Preamble of the study is devoted to defining the concept of the mask, and exploring its historical origins that dated back to those primitive religious rituals, and its move to the theater, Then it speaks about its literality after being used by great Western poets, then it moved to Arab poetry by modernist poets. After that, it discusses its separating limits with other techniques that are all aiming to the return to the heritage and recalling historical figures. The first chapter was limited to the motives of using mask technique in contemporary Arabic Poetry, types and efficiency of masks. The second chapter aimed to detect the mask technique and the prophetic mask in contemporary Algerian Arabic poetry by approaching poetic texts by our poets LAKHDAR FELLOUS and OTHMAN LOUCIF, which rose to the technique of wearing masks of characters of the prophets Nuh, Ayyub, Mussa and Ibrahim, peace be upon them and the last of the prophets and messengers peace be upon him. While the third and last chapter tried to investigate the mask poem structure. The selected models had distinctive characteristics, combining lyricism, drama, subjective and objective characteristics at the same time. The forms of benefit from the personal experience of the mask differed, between evoking an integral attitude or a partial attitude or vocabulary. Also, this type of wearing a mask gave to the selected mask poems artistic characteristics such as deepening the connotation and adding huge dramatic potentials besides transcending the limits of time, these aesthetics that were not to be as deep and artistic without wearing the mask of these religious figures.
Keywords: القناع / الشعر الجزائري المعاصر /الرمز/ استدعاء شخصيات الأنبياء